2017
DOI: 10.1186/s40463-016-0181-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular mapping of the retroauricular skin – proposal for a posterior superior surgical incision for transcutaneous bone-conduction hearing implants

Abstract: BackgroundPassive transcutaneous osseointegrated hearing implant systems have become increasingly popular more recently. The area over the implant is vulnerable due to vibration and pressure from the externally worn sound processor. Good perfusion and neural integrity has the potential to reduce complications. The authors’ objective was to determine the ideal surgical exposure to maintain perfusion and neural integrity and decrease surgical time as a result of reduced bleeding.MethodsThe vascular anatomy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…• The Osia system is a new, safe and powerful transcutaneous active bone-conduction hearing implant • This study directly compared the performance of the BAHA Attract and Osia systems in the same individual • From an audiological perspective, the Osia system provides better outcomes compared with the passive transcutaneous Attract system, especially at higher frequencies • The difference between the first-and second-generation Osia system is only the structural design of the implant • Therefore, the long-term results with the first generation likely reflect the performance of both systems Previously, our department developed a minimally invasive surgical technique based on a multimodal morphometric study of the temporal soft tissue area. 9 In that particular study, we demonstrated that when the incision is placed superior-posterior to the Attract position it does not compromise the macrocirculation of the peri-implant area, which contributed to fewer post-operative healing problems. When implanting the Osia system, we positioned the incision similarly (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…• The Osia system is a new, safe and powerful transcutaneous active bone-conduction hearing implant • This study directly compared the performance of the BAHA Attract and Osia systems in the same individual • From an audiological perspective, the Osia system provides better outcomes compared with the passive transcutaneous Attract system, especially at higher frequencies • The difference between the first-and second-generation Osia system is only the structural design of the implant • Therefore, the long-term results with the first generation likely reflect the performance of both systems Previously, our department developed a minimally invasive surgical technique based on a multimodal morphometric study of the temporal soft tissue area. 9 In that particular study, we demonstrated that when the incision is placed superior-posterior to the Attract position it does not compromise the macrocirculation of the peri-implant area, which contributed to fewer post-operative healing problems. When implanting the Osia system, we positioned the incision similarly (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…The 8 cm C-shape incision recommended for BAHA Attract includes horizontal components. Confection of cutaneous flap can potentially compromise the parieto-temporal vascularization by horizontally crossing two major arteries, the posterior branch of the superficial temporal artery and the posterior auricular artery, as described by Perenyi et al [14]. MIP technique does not require skin flap confection; consequently, we believe that cutaneous necrosis [15,18] is unlikely.…”
Section: Discussionmentioning
confidence: 76%
“…Recommended surgery also requires the creation of a skin flap, together with bone drilling to smooth out the area for bedding the internal magnetic implant, and the use of a screw fixation system (BI300) titanium implant to attach the magnet to the bone. In case of skin exceeding 6 mm thickness, the manufacturer recommends flap thinning [14].…”
Section: Introductionmentioning
confidence: 99%
“…tes anatómiai, cadaverszektoranalízis-vizsgálataink alapján a fontosabb ér-és idegképletek sérülése így a legnagyobb valószínűséggel elkerülhetővé válik [16]. A műtéteket 5 mm-es implantátummal végeztük.…”
Section: Eredeti Közleményunclassified
“…Előzetes anató-miai, cadaver-szektoranalízises vizsgálataink alapján így elkerülhetővé vált a fontosabb ér-és idegképletek iatrogén sérülése. Ezáltal az implantátum feletti bőrlebeny vitalitása javult, valamint jelentősen csökkent az operált terület bőrének érzéketlensége [16]. Ez összhangban van korábbi megfigyelésünkkel, amelyben a periimplant terület vascularis, illetve neuralis integritásának megőrzé-sét kiemelten fontos tényezőnek találtuk a posztoperatív sebgyógyulás folyamatában.…”
Section: Megbeszélésunclassified